Giant photostriction in organic–inorganic lead halide perovskites - Yang Zhou (Nature Portfolio, 2016)
The photophysics of lead halide perovskites is under intense investigation. Here, the authors use force microscopy on single crystals to show that light induces drastic lattice changes, and propose that the weakening of the hydrogen coupling under illumination is responsible for the lattice dilatation.